Prebiotic fiber blend supports growth and development and favorable digestive health in puppies - McGrath, Allison P.; Motsinger, Laura A.; Brejda, John; Hancock, Leslie (Frontiers in Veterinary Science, 2024)
Introduction A healthy gastrointestinal (GI) microbiome has been shown to be essential for proper nutrient absorption and metabolism, maintenance of intestinal epithelial integrity and osmolarity, gut immunomodulation, and overall health. One of the most effective ways to promote a healthy GI microbiome is through dietary interventions, such as the addition of prebiotics. Prebiotics are substrates that are selectively utilized by the host GI microbiome through fermentation to confer a health benefit. However, research on prebiotics in companion animals is limited, especially in growing animals. Thus, this study was conducted to assess the effects of a novel prebiotic fiber blend on key parameters related to intestinal health and growth in puppies. Methods Twenty-two puppies at least 4 months of age but not older than 10 months were fed a commercially available dry food during a prefeed period, and then fed a similarly formulated test food with the addition of the prebiotic fiber blend for a minimum of 90 days. Serum and fecal samples were collected at the end of the prefeed period and throughout the test period. Results Puppies fed the test food grew as expected for puppies of this age. Complete blood count and serum chemistry analyses were clinically normal for all animals. Fecal score increased linearly, fecal moisture decreased linearly, and pH exhibited a cubic trend throughout the study duration. There was a linear increase in short-chain fatty acids throughout the study, which is associated with favorable digestive and overall health. The inflammatory cytokine interleukin-7 decreased linearly and interleukin-18 trended towards linear decrease. Conclusion This study showed that puppies continued to grow and develop normally, and experienced serum and stool characteristics indicative of improved GI health when fed a growth food fortified with a novel prebiotic fiber blend. Furthermore, these results contribute to the overall understanding of the effects of prebiotics on the GI health of growing companion animals.